Soil Properties‐Based Targeting of Soil Conditioners for Reduced Phosphorus Loading From Agriculture - Keskinen, Riikka; Soinne, Helena; Uusitalo, Risto; Ekholm, Petri; Räsänen, Timo A.; Uusi‐Kämppä, Jaana; Bergholm, Jenna; Nikama, Johanna; Hyväluoma, Jari (Wiley-Blackwell, 2025)
Soil conditioning materials, gypsum, structure lime and pulp and paper mill sludges, have emerged as promising means to combat soil losses for protecting waterways. The mechanisms of impact vary between these materials, whereby the selection of the most efficient product depends on the soil type. In this paper, a soil-properties based selection method was developed for these three soil conditioners focusing on water quality impacts, specifically on particle associated phosphorus (P) losses that make the major share of the P transfer to the eutrophied Archipelago Sea. For targeting soil conditioner applications, a risk grading protocol identifying field parcels with the highest emission potential was formulated. The soil features considered in the risk grading were soil P status, aggregate stability, erosion potential, and typical soil management. In assessing the suitability of the individual soil conditioners, the soil properties considered were electrical conductivity (EC), pH, concentrations of exchangeable calcium (Ca) and magnesium (Mg), soil test P, clay percentage, organic carbon (C) content, and the ratio of clay/C. The method was applied in the Savijoki catchment in Southwest Finland mainly consisting of relatively flat, non-calcareous clay soils low in soil test P and high in clay/C ratios. Phosphorus emission risk in the area was estimated to be moderate though sporadic high-risk areas were identified. The applied selection criteria targeted fibres to 61%, structure lime to 29% and gypsum to 11% of the case study area. High clay/C ratio favoured fibres, whereas gypsum and structure lime were limited to soils with low EC. The proposed method provides means for farmers and advisors to select the most suitable soil conditioner for a given soil. For decision-makers, the method offers an instrument for policy recommendations serving, for example, in directing environmental subsidies. The method is applicable beyond the Archipelago Sea region though the suggested limit values need to be adjusted site-specifically.
Keywords: soil conditioners; soil losses; phosphorus; water quality